A new method of hulling oil seeds in Ukraine - Perevalov, Leonid; Piven, O. M. (MDPI, 2024)
The purpose of this study is to find a new method of seeds dehulling when the seeds are cooled to sub-zero temperatures.
Keywords: safflower; seed dehulling; hulling; single oriented strike method